Jawāmiʿ al-kalim: revisiting the concept in traditional, intellectual and mystical discourse - Jamil, Khairil Husaini (2019)
The paper will explore the concept of jawāmiʿ al-kalim as it appears in various genres of literature. Basically, jawāmiʿ al-kalim is an attribute used to qualify the words of Prophet Muhammad SAW. In a ḥadīth, the Prophet was reported to proclaim that he was given jawāmiʿ al-kalim. This study will try to gather the view of scholars on the meaning of jawāmiʿ al-kalim and analyse the influence of their disciplinary background to their interpretation of the term. The main groups of concern are the muḥaddithūn, the fuqahāʾ, the theologians, and the Ṣūfis. As jawāmiʿ al-kalim is closely attached to the domain of words and speeches, an attempt will be made as well to investigate how the concept can be applied for educating higher order elocution skill and the speaking manner in Islam.